2016
DOI: 10.3348/kjr.2016.17.5.763
|View full text |Cite
|
Sign up to set email alerts
|

CT-Guided Radiofrequency Ablation of T1a Renal Cell Carcinoma in Korea: Mid-Term Outcomes

Abstract: ObjectiveTo evaluate the mid-term outcomes of percutaneous radiofrequency ablation (RFA) treatment in patients with small (< 4 cm) renal cell carcinoma (RCC) in Korea.Materials and MethodsBetween 2010 and 2015, 51 patients (40 men and 11 women; median age, 57 years) with biopsyproven 51 RCC were treated using CT-guided RFA. All patients were clinically staged T1aN0M0 prior to RFA. The median tumor size and follow-up period were 2.1 cm (range, 1.0–3.9 cm) and 26 months (4–60 months), respectively. Local tumor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…In 1997, Zlotta et al, reported the first use of image-guided radiofrequency ablation in the treatment of a renal cancer [23], and nowadays this technique is included as a potential treatment in several guidelines by urological and radiological societies [17,24,25]. At the present, the majority of literature on the topic is based on small retrospective study, generally with short follow-up, and clinical series are based on US or CT guided ablations [8][9][10][11][12][13][14][15]. One of the key technical aspects to improve the results of ablation is the reliability of the image guidance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1997, Zlotta et al, reported the first use of image-guided radiofrequency ablation in the treatment of a renal cancer [23], and nowadays this technique is included as a potential treatment in several guidelines by urological and radiological societies [17,24,25]. At the present, the majority of literature on the topic is based on small retrospective study, generally with short follow-up, and clinical series are based on US or CT guided ablations [8][9][10][11][12][13][14][15]. One of the key technical aspects to improve the results of ablation is the reliability of the image guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Among different ablative techniques, radiofrequency ablation (RFA) has been one of the first applied in the treatment of kidney cancer [8,10,11]. Ultrasound (US), providing real time visualization, represents the most widely used technique for guiding ablations in the abdomen, particularly in Europe and Asia [12,13], while computed tomography (CT) is preferred in several centers, mainly in the United States [14,15]. Combination of US and a cross-sectional imaging modality such as CT might improve the visualization during treatment and improve results and safety of the procedure [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…An interventional radiologist had experienced 7-year RFA experience before treating the first case in our study. All of these patients were also evaluated in another study in terms of midterm RFA outcomes [12].…”
Section: Methodsmentioning
confidence: 99%
“…Radiofrequency ablation (RFA) is a relatively novel percutaneous technique, which has been widely applied for the treatment of several different medical conditions including cancers [2][3][4] and cardiac arrhythmias [5]. More recently, RFA has also been applied to treat chronic pain originating form benign conditions (e.g.…”
Section: Commentarymentioning
confidence: 99%